(untitled) (Journal of Educational Sciences, 2018)
The article raises the problem of understanding the role of reflection in professional pedagogical activity. The urgency of diagnostics and formation of pedagogical reflection of trainee students is revealed. The author substantiates the possibility of managing the development of pedagogical reflection in undergraduate students in conditions of specially organized pedagogical activity. Described specifically designed tasks aimed at developing personal and communicative reflection of student interns. Approved methods of forming skills of personal and communicative reflection, proof of their effectiveness are presented. Taking into account the results of the conducted research, some recommendations are proposed, aimed at increasing the effectiveness of teaching students-trainees to the skills of pedagogical reflection. Effective ways of forming personal reflection skills, according to teachers, are the following exercises: «The picture of the future» (for 100% of student trainees); «Monitoring motivation» (96%); «Mini-program » (87%); «Symbol of life success» (84%); «My achievements in life and profession» (68%); «The solution of life and professional problems» (68%); «My ideal of the professor» (66%); «Values of professional life» (65%); Resource (63%); «Pyramid of professional growth» (52%). Student interns indicated the following effects of these methods: the opportunity to re-evaluate the negative past experience and find in it a positive incentive for development; a concrete definition of the ways of the current self-control of motivation and behavior, ways of coping with life and professional problems, ways and means of selfdevelopment; the formation of a clear desired image of oneself in the future, a significant deepening of the various ideas about oneself, his «I», his inner world, the concretization and adjustment of the «image of the I»; strengthening the skills of effective self-analysis. Key words: pedagogical reflection, personal and communicative reflection, reflexive skills, selfknowledge, self-esteem, self-reflection, self-correction.